Chronic stress enhances glycolysis and promotes tumorigenesis - Qin, Qiufeng; Li, Shuying; Zhong, Yixuan; Bai, Jing; An, Lin; Yang, Lei; Gu, Wei; Deng, Di; Zhao, Jinlan; Zhang, Rong; Liu, Haiquan; Bai, Shasha (Frontiers in Oncology, 2025)
Depression is a well-known risk factor for tumors, but the mechanisms other than inflammation are unclear. Aerobic glycolysis is considered to be a critical element in the reprogramming of energy metabolism in malignant tumors, and impaired glycolysis has been reported in the brains of chronic stress mice. Therefore, this study aimed to explore the role of glycolysis in which depression promotes tumorigenesis. We examined the impacts of chronic unpredictable mild stress (CUMS) on the growth and metastasis of breast cancer (BC) and lung cancer (LC). CUMS was used to construct a mouse depression model, BALB/c mice were injected with 4T1-Luc cells in the right subcutaneous mammary fat pad, and C57BL/6 mice were injected with Lewis-Luc cells in the tail vein. The experiments were conducted through behavioral experiments, live imaging techniques of small animals, Western blot, Glycolytic metabolites measurement, Hematoxylin and eosin staining (H&E staining), Nissl staining, and immunohistochemical (IHC) tests. The findings showed that both CUMS and tumors induced depressive-like behavior, neuronal damage, and impaired synaptic plasticity in mice, while CUMS also enhanced tumor development and metastasis in both BC and LC. In the brain, both CUMS and tumor alone and in combination less influence glycolytic products and enzyme levels. However, CUMS significantly enhanced the levels of aerobic glycolytic products and enzymes in tumor tissue. Collectively, our results provide insights into how glycolysis is regulated in the brain, leading to depression-like behavior, and how depression, in turn, enhanced glycolysis and promoted tumorigenesis.